Synchrotron radiation from the NESTOR storage ring - Karnaukhov, I.M.; Moskalets, N.V.; Shcherbakov, A.A. (Вопросы атомной науки и техники, 2007)
The main characteristics of synchrotron radiation from the generator X–ray NESTOR are presented. NESTOR is a New Electron Storage Ring with electron energy from 40 up to 225 MeV and circumference 15.418m. Areas of application of photon beams from infrared up to vacuum ultraviolet region are considered in the work.